A Phenomenological Study of Islamic Religious Education Teachers' Experiences in Inclusive Classrooms at Sleman Elementary Schools - Iffah Khoiriyatul Muyassaroh; Sibawaihi; Sukiman; Wahyu Nurrohman (PLD UIN Sunan Kalijaga, 2025)
This study explores the experiences of Islamic Religious Education (PAI) teachers in delivering inclusive instruction at elementary schools in Sleman, Indonesia. Employing a qualitative phenomenological approach, data were gathered through interviews, classroom observations, and document analysis involving five educators across three schools. The findings reveal that inclusive practices in PAI are facilitated through collaboration among PAI teachers, classroom teachers, and Special Companion Teachers (GPK), as well as the use of individualized strategies and multimedia resources. However, challenges persist, including limited infrastructure, lack of inclusive training, and insufficient parental involvement. The study highlights the need for systemic support, capacity building, and inclusive pedagogical innovation. It contributes to the discourse on inclusive religious education by integrating theological values with inclusive practices, offering implications for policy development and teacher training. Penelitian ini mengkaji pengalaman guru Pendidikan Agama Islam (PAI) dalam melaksanakan pembelajaran inklusif di sekolah dasar di Kabupaten Sleman, Indonesia. Menggunakan pendekatan kualitatif fenomenologis, data dikumpulkan melalui wawancara, observasi kelas, dan analisis dokumen terhadap lima pendidik dari tiga sekolah. Hasil penelitian menunjukkan bahwa praktik inklusif dalam pembelajaran PAI diwujudkan melalui kolaborasi antara guru PAI, guru kelas, dan Guru Pendamping Khusus (GPK), serta penerapan strategi individual dan pemanfaatan media pembelajaran yang beragam. Namun demikian, tantangan tetap muncul, seperti keterbatasan sarana prasarana, minimnya pelatihan inklusif, dan rendahnya keterlibatan orang tua. Studi ini menekankan pentingnya dukungan sistemik, peningkatan kapasitas guru, dan inovasi pedagogi inklusif. Kontribusi penelitian ini terletak pada pengintegrasian nilai-nilai keagamaan dengan praktik inklusif, yang memberikan implikasi bagi pengembangan kebijakan dan pelatihan guru.